Association of the delayed changes in glutamate levels and functional connectivity with the immediate network effects of S-ketamine - Danyeli, Lena Vera; Sen, Zümrüt Duygu; Colic, Lejla; Kurzweil, Lisa; Gensberger-Reigl, Sabrina; Macharadze, Tamar; Götting, Florian; Refisch, Alexander; Liebe, Thomas; Chand, Tara; Kretzschmar, Moritz; Wagner, Gerd; et al. (Translational Psychiatry, 2023)
Ketamine shows rapid antidepressant effects peaking 24 h after administration. The antidepressant effects may occur through changes in glutamatergic metabolite levels and resting-state functional connectivity (rsFC) within the default mode network (DMN). A multistage drug effect of ketamine has been suggested, inducing acute effects on dysfunctional network configuration and delayed effects on homeostatic synaptic plasticity. Whether the DMN-centered delayed antidepressant-related changes are associated with the immediate changes remains unknown. Thirty-five healthy male participants (25.1 ± 4.2 years) underwent 7 T magnetic resonance spectroscopy (MRS) and resting-state functional magnetic resonance imaging (rsfMRI) before, during, and 24 h after a single S-ketamine or placebo infusion. Changes in glutamatergic measures and rsFC in the DMN node pregenual anterior cingulate cortex (pgACC) were examined. A delayed rsFC decrease of the pgACC to inferior parietal lobe (family-wise error corrected p (pFWEc) = 0.018) and dorsolateral prefrontal cortex (PFC; pFWEc = 0.002) was detected that was preceded by an immediate rsFC increase of the pgACC to medial PFC (pFWEc < 0.001) and dorsomedial PFC (pFWEc = 0.005). Additionally, the immediate rsFC reconfigurations correlated with the delayed pgACC glutamate (Glu) level increase (p = 0.024) after 24 h at trend level (p = 0.067). Baseline measures of rsFC and MRS were furthermore associated with the magnitude of the respective delayed changes (p’s < 0.05). In contrast, the delayed changes were not associated with acute psychotomimetic side effects or plasma concentrations of ketamine and its metabolites. This multimodal study suggests an association between immediate S-ketamine-induced network effects and delayed brain changes at a time point relevant in its clinical context.
CRIS-Team Scopus Importer:2023-03-03